Obesity in Midlife Hampers Resting and Sensory‐Evoked Cerebral Blood Flow in Mice. Issue 1 (10th November 2020) - Soleimanzad, Haleh; Montaner, Mireia; Ternier, Gaëtan; Lemitre, Mathilde; Silvestre, Jean‐Sébastien; Kassis, Nadim; Giacobini, Paolo; Magnan, Christophe; Pain, Frédéric; Gurden, Hirac
Abstract : Objective: This study aimed to investigate the effects of a high‐fat diet (HFD) and aging on resting and activity‐dependent cerebral blood flow (CBF). Methods: To run a comparison between obese and age‐matched control animals, 6‐week‐old mice were fed either with regular chow or an HFD for 3 months or 8 months. Glucose tolerance and insulin sensitivity were assessed for metabolic phenotyping. Resting and odor‐evoked CBF at the microvascular scale in the olfactory bulb (OB) was investigated by multiexposure speckle imaging. Immunolabeling‐enabled imaging of solvent‐cleared organs was used to analyze vascular density. The ejection fraction was studied by using cardioechography. Olfactory sensitivity was tested by using a buried‐food test. Results: Glucose intolerance and compromised odor‐evoked CBF were observed in obese mice in the younger group. Prolonged HFD feeding triggered insulin resistance and stronger impairment in activity‐dependent CBF. Aging had a specific negative impact on resting CBF. There was no decrease in vascular density in the OB of obese mice, although cardiac function was impaired at both ages. In addition, decreased olfactory sensitivity was observed only in the older, middle‐aged obese mice. Conclusions: OB microvasculature in obese mice showed a specific functional feature characterized by impaired sensory‐evoked CBF and a specific deleterious effect of aging on resting CBF.